Prevalencia de enteroparasitos, rotavirus y adenovirus en niños aparentemente sanos - Rivero de R Zulbey; Maldonado I Adriana; Bracho M Angela; Castellanos S María; Torres Yessica; Costa-León Luciana; Méndez V Angie; Márquez A Lideivis (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2009)
Abstract: To determine the prevalence of intestinal parasites, rotavirus and adenovirus in apparently healthy children, a parasitological study of 101 fecal samples from persons between 2 months and 14 years from both sexes was performed, as well as a virological study of 70 samples of less than 5 years of age. For each fecal specimen, a direct coproparasitological examination was performed, with Formol - Ether concentration and Modified Zielh-Nielsen tincture techniques was made. To determine the Rotavirus and Adenovirus, the immunoenzymatic assay technique (ELISA) was used. The Ji-square (c2) and the Z test were used for statistical analysis. A high percentage of people with parasites was found (85.15%). The most frequent protozoan species were: Blastocystis hominis (52.47%), Giardia lamblia (26.73.%) and Entamoeba coli (20.79%); among the helminthes were Trichuris trichiura (50.49%), Ascaris lumbricoides (48.51%) and Strongyloides stercoralis (7.92%). Rotavirus frequency was 2.86%, while Adenovirus infection was absent. The high prevalence of parasites demonstrates unhealthy conditions in the community; despite these, the opposite occurred regarding the virus being studied. Perhaps the acquisition of antibodies through maternal lactation influenced the Rotovirus percentages, whereas development of antibodies at an early age probably influenced the enteric Adenovirus. Resumen: Para determinar la prevalencia de parásitos intestinales, rotavirus y adenovirus en niños aparentemente sanos, se realizó el estudio parasitológico de 101 muestras fecales de individuos de uno u otro sexo, con edades comprendidas entre 2 meses y 14 años, así como el estudio virológico en 70 muestras de los niños menores de 5 años. A cada espécimen fecal se le realizó un examen coproparasitológico directo, concentración de Formol-Éter y coloración de Kinyoun. Para determinar Rotavirus y Adenovirus se empleó la técnica de Ensayo Inmunoenzimático (ELISA). Para el análisis estadístico se utilizó el Ji-cuadrado (x2) y la prueba Z. Se observó un elevado porcentaje de individuos parasitados (85,15%), los protozoarios más frecuentes fueron: Blastocystis hominis (52,47%), Giardia lamblia (26,73%) y Entamoeba coli (20,79%) y entre los helmintos Trichuris trichiura (50,49%), Ascaris lumbricoides (48,51%) y Strongyloides stercoralis (7,92%). Se observó una frecuencia de Rotavirus del 2,86% y ausencia de infección por Adenovirus. La elevada prevalencia parasitaria demuestra las condiciones de insalubridad de la comunidad, a pesar de ello, lo contrario ocurrió con los virus estudiados. Para Rotavirus quizás influyó la adquisición de anticuerpos a través de la lactancia materna, mientras que, para Adenovirus entéricos, probablemente el desarrollo de anticuerpos a edad temprana.